2017
DOI: 10.4172/2329-8901.1000182
|View full text |Cite
|
Sign up to set email alerts
|

Antibiofilm and Antiadhesive Activities of Different Synbiotics

Abstract: Synbiotics are a combination of probiotic bacteria and the growth promoting prebiotic ingredients that purport "synergism".Probiotics are well known for their ability to restore a healthful balance of commensal microbes supporting the repair of hyper-permeable epithelial barriers and interfering with infection. The present research was designed to evaluate the anti-virulence role of cell-free supernatants of synbiotic cultures.The effect of prebiotics fructo-oligosaccharide, inulin and isomaltose on probiotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 34 publications
3
12
0
Order By: Relevance
“…Other authors proved that metabolites from S. boulardii had a bacteriostatic effect on cells of S. aureus in amount of 0.1 mL and showed no activity against E. coli (Stefania et al, 2017). Individual sensitivity of test cultures to substances of saccharomycetes, observed by Stefania et al (2017), has been confirmed by our results. The polyresistant strain K. pneumoniae PR demonstrated higher sensitivity to biologically active substances of L. rhamnosus GG compared to disintegrates and metabolites from S. boulardii.…”
Section: Discussionsupporting
confidence: 82%
“…Other authors proved that metabolites from S. boulardii had a bacteriostatic effect on cells of S. aureus in amount of 0.1 mL and showed no activity against E. coli (Stefania et al, 2017). Individual sensitivity of test cultures to substances of saccharomycetes, observed by Stefania et al (2017), has been confirmed by our results. The polyresistant strain K. pneumoniae PR demonstrated higher sensitivity to biologically active substances of L. rhamnosus GG compared to disintegrates and metabolites from S. boulardii.…”
Section: Discussionsupporting
confidence: 82%
“…As shown in Fig. 2, cell-free extract B in the composition of the cultivation medium at a concentration of 10 % does not have a significant effect on the optical density gain of the culture compared to PC 10 . An increase in the content of this extract in the composition of the cultivation medium to 30 % and 50 % leads to a significant increase of the culture optical density gain compared to the PC 30 and PC 50 (StIs are 19.5 % and 16.3 %, respectively).…”
Section: Resultsmentioning
confidence: 86%
“…One way to increase the survival of bacteria is to protect them by encapsulation or adhesion to a semi-permeable biocompatible dextranomer microsphere in the form of a biofilm [8]. The second way is to use growth promoting prebiotic ingredients: β-galacto-oligosaccharides, lactulose, fructo-oligosaccharides, inulin, isomaltose [10]. An alternative approach to increasing colonization of the gastrointestinal tract by beneficial microorganisms and enhancing the protective properties of the immune system is using the biological activity of the probiotics' derivatives [11][12][13].…”
mentioning
confidence: 99%
“…Mamianas et al stated that L. plantarum has good antimicrobial effects against S. aureus, E. coli and Bacillus subtilis [33]. To date, only a few carbohydrates have been defined and reported as prebiotics, including inulin, lactulose, β-galacto-oligosaccharides, and fructooligosaccharides [29]. In the present study, raffinose, trehalose, riboflavin, citrate, inulin, and sorbitol was used as prebiotic.…”
Section: Discussionmentioning
confidence: 94%
“…Antibacterial activity (MIC and MBC) of cell-free supernatants of probiotics growth in absence or in presence of prebiotics against clinical isolates of MDR A. baumannii were shown in Table 3. The MIC was recorded as µl of bacterial culture supernatants at a concentration of 10 8 bacteria/ml [29]. All probiotics exhibited an antibacterial effect against MDR A. baumannii.…”
Section: Micro-broth Dilution Methodsmentioning
confidence: 99%